Artificial intelligence in the age of neural networks and brain computing - Kozma, Robert; Alippi, Cesare; Choe, Yoonsuck; Morabito, F. C. (Francesco Carlo) (Academic Press, an imprint of Elsevier, 2019)
With contributions from pioneers and experts in the field of neural networks, this book covers the major basic ideas of brain-like computing behind AI, provides a framework to deep learning, and launches novel and intriguing paradigms as future alternatives. --